Use of Case Study Technology in Improving Practical Courses in Nuclear Physics - K. R. Nasriddinov; R. V. Qosimjonov (Zien Journals, 2022)
This article is devoted to the use of case-study technology in improving practical training in nuclear physics, and the aspect of increasing efficiency using case-study technology in passing practical training in the department of nuclear physics is analyzed.
Keywords: case study; individual; communication; intellectual